Isolation, genome analysis and tissue localization of ceratobasidium theobromae, a new encounter pathogen of cassava in Southeast Asia - Gil-Ordóñez, Alejandra; Pardo, Juan M; Sheat, Samar; Xaiyavong, Khamla; Leiva, Ana M.; Arinaitwe, Warren; Winter, Stephan; Newby, Jonathan; Cuellar, Wilmer J. (Nature Portfolio, 2024)
In Southeast Asia (SEA) fastidious fungi of the Ceratobasidium genus are associated with proliferation of sprouts and vascular necrosis in cacao and cassava, crops that were introduced from the tropical Americas to this region. Here, we report the isolation and in vitro culture of a Ceratobasidium sp. isolated from cassava with symptoms of witches' broom disease (CWBD), a devastating disease of this crop in SEA. The genome characterization using a hybrid assembly strategy identifies the fungus as an isolate of the species C. theobromae, the causal agent of vascular streak dieback of cacao in SEA. Both fungi have a genome size > 31 Mb (G+C content 49%), share > 98% nucleotide identity of the Internal Transcribed Spacer (ITS) and > 94% in genes used for species-level identification. Using RNAscope® we traced the pathogen and confirmed its irregular distribution in the xylem and epidermis along the cassava stem, which explains the obtention of healthy planting material from symptom-free parts of a diseased plant. These results are essential for understanding the epidemiology of CWBD, as a basis for disease management including measures to prevent further spread and minimize the risk of introducing C. theobromae via long-distance movement of cassava materials to Africa and the Americas.